Kilka uwag na tle aktualnych przemian konstytucyjnych w Polsce - Szmyt, Andrzej; Rytel-Warzocha, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
In 2015, right – wing parties came to power. They did not get the majority needed to change the Constitution, but they obtained an absolute majority of seats in the parliament that allowed to create their own government and to adopt laws. By means of legislation and practice, the process of the destruction of the constitutional system began that was accompanied by the strong emphasis of the fact that the parliamentary majority represents the Sovereign (people). Such approach leads them to the conclusion that the instruments to control the parliament should be eliminated. Using law to paralyze the Constitutional Tribunal has become symbolic as well as the refusal to publish some of the judgments of the Constitutional Tribunal. By law, the foundations of the rule of law, division of powers and judicial independence were violated. Through legislative changes the Public Prosecutor's Office was subordinated to executive power and the Minister of Justice obtained a significant influence on the functioning of the common judiciary. The process of legal changes has been accompanied by the political practice of making fundamental decisions outside state organs, with disregard for democratic standards as well as populist social and political rhetoric. The practice of referring to "supraposition" of the parliament fits into the long-term tradition of the "priority" role of the representative bodies - still from the First Republic, then the March Constitution of 1921, and finally the times of the People's Republic of Poland with the constitutional principle of unity (instead of division) of power and the superior position of the unicameral Sejm. During the Second Republic the democratic restrictions - after the May 1926 coup – were caused by the appeal of the ruling camp to charismatic legitimization of Józef Piłsudski. A reference to this part of interwar history is an important motive for the ideology of the leader of the current ruling majority. It’s supplemented by the concept of the "political decision-making center" of the state, located outside the state apparatus, anchored in the facade of constitutional solutions from the period of the socialist system.
Keywords: commemorative book; constitutionalism; Constitution; democracy; human rights; right to court; freedoms and rights